Direct thermal charging cell for converting low-grade heat to electricity - Wang, Xun; Huang, Yu-Ting; Liu, Chang; Mu, Kaiyu; Li, Ka Ho; Wang, Sijia; Yang, Yuan; Wang, Lei; Su, Chia-Hung; Feng, Shien-Ping (Nature communications, 2019)
Efficient low-grade heat recovery can help to reduce greenhouse gas emission as over 70% of primary energy input is wasted as heat, but current technologies to fulfill the heat-to-electricity conversion are still far from optimum. Here we report a direct thermal charging cell, using asymmetric electrodes of a graphene oxide/platinum nanoparticles cathode and a polyaniline anode in Fe 2+ /Fe 3+ redox electrolyte via isothermal heating operation. When heated, the cell generates voltage via a temperature-induced pseudocapacitive effect of graphene oxide and a thermogalvanic effect of Fe 2+ /Fe 3+ , and then discharges continuously by oxidizing polyaniline and reducing Fe 3+ under isothermal heating till Fe 3+ depletion. The cell can be self-regenerated when cooled down. Direct thermal charging cells attain a temperature coefficient of 5.0 mV K −1 and heat-to-electricity conversion efficiency of 2.8% at 70 °C (21.4% of Carnot efficiency) and 3.52% at 90 °C (19.7% of Carnot efficiency), outperforming other thermoelectrochemical and thermoelectric systems. Recovery of low-grade heat can aid in reducing greenhouse gas emissions, but heat-to-electricity conversion technologies should be optimized. Here the authors report a direct thermal charging cell that uses asymmetric electrodes and a redox electrolyte to efficiently convert low-grade heat into electricity.